Atypical Intramuscular Myxoma of the Lumbosacral Paraspinal Muscle: The First Case Report in Asian - Choi, Doo Yong (J Korean Neurosurg Soc, 2015)
Intramuscular myxoma (IM) is a benign neoplasm of mesenchymal origin. We report a rare case of IM which was located in the lumbosacral paraspinal muscles. A 62-year-old female patient presented with progressive low back pain for 2 months, and the radiologic findings showed a large mass (4.0×3.5×6.5 cm) in the right lumbosacral paraspinal area. Total resection of the tumor was performed and the symptom was nearly resolved after surgery. Although the immuno-histopathological analysis was consistent with IM, there were some different findings from typical pathological characteristics of IM in this case. Firstly, the symptomatic change of the mass took relatively short time (less than 3 months), and this change was accompanied by partial calcification inside the mass. Moreover, iatrogenic interruption of paravertebral muscle by the other previous operation might be the promoting factor of the fibrous dysplasia, which can explain the pathogenesis of IM. To our knowledge, this is the eighth case of the lumbar paraspinal myxoma reported in the literatures and the first case in Asian population.